2021
DOI: 10.1016/j.ijchy.2021.100088
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 morbidity and mortality associated with angiotensin-converting enzyme inhibitors or angiotensin receptor blockers use among 14,129 patients with hypertension from a US integrated healthcare system

Abstract: Objective Although recent evidence suggests no increased risk of severe COVID-19 outcomes associated with angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) use, the relationship is less clear among patients with hypertension and diverse racial/ethnic groups. This study evaluates the risk of hospitalization and mortality among patients with hypertension and COVID-19 in a large US integrated healthcare system. Methods Patients with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Recently published studies do have larger patient numbers. One such study supported by the American Heart Association's Rapid Response Grant COVID-19 is by An et al [50], with 4,652 patients on ACEI and 2,546 on ARB. However, this is still lower than the number of patients observed in our study, 97,843 on ACEI and 83,290 on ARB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies do have larger patient numbers. One such study supported by the American Heart Association's Rapid Response Grant COVID-19 is by An et al [50], with 4,652 patients on ACEI and 2,546 on ARB. However, this is still lower than the number of patients observed in our study, 97,843 on ACEI and 83,290 on ARB.…”
Section: Discussionmentioning
confidence: 99%
“…Recent randomized controlled trials testing continuation vs. discontinuation of ACEI/ARB therapy have suggested no differential risk of infection or COVID-19 severity between these strategies [3] , [4] . Results from the observational studies have been much more variable, with some suggesting substantially lower mortality (~50–60% risk reductions) for ACEI/ARB users vs. non-users [5] , [6] , [7] , whereas others have suggested higher risk of mortality [8] . However, many of these studies have significant methodologic limitations [9] , and are limited by their homogenous populations, making interpretation and generalizability difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that look at the impact of ACEIs in the treatment of hypertensive patients with COVID‐19 have not discriminated between ARBs and ACEIs but are associated with the significant reduction in all‐cause mortality (OR = 0.5, 95%, CI: 0.34, 0.72) 88 …”
Section: Repurposing Drugs To Treat Covid‐19mentioning
confidence: 99%
“…However, ACEIs elevate concentrations of bradykinin, which have vasodilatory effects on cardiovascular tissues which could be beneficial in the morbidity associated with COVID-19. Studies have shown that treatment with ACEIs or ARBs is associated with a similar reduction in morbidity and mortality from COVID-19.Most studies that look at the impact of ACEIs in the treatment of hypertensive patients with COVID-19 have not discriminated between ARBs and ACEIs but are associated with the significant reduction in all-cause mortality (OR = 0.5, 95%, CI: 0.34, 0.72) 88. Hippisley-Cox 89 recently reported a study of over 8 000 000 people, of whom 19 486 had COVID-19 and 1286 received ICU care, 7.8% were treated with an ACEI and 3.7% with an ARB.…”
mentioning
confidence: 99%